Nursing student attitudes toward dying patient care: A European multicenter cross-sectional study - Ferri, Paola; Di Lorenzo, Rosaria; Stifani, Serena; Morotti, Elena; Vagnini, Matilde; Jiménez Herrera, María Francisca; Bonacaro, Antonio; Artioli, Giovanna; Rubbi, Ivan; Palese, Alvisa (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the workNursing education plays a key role in preparing future nurses to deal with dying patients, which represents one of the most emotionally involving aspect of nursing. The aims of the study were to explore nursing students’ attitudes towards care of dying patients in three different European contexts and to analyze the variables that can influence them.MethodsWe conducted an international multicenter cross-sectional study. We administered the Frommelt Attitude Toward Care of the Dying Scale form B (FATCOD-B) and a demographic form to 569 students, enrolled in the Nursing Programmes in three different countries (Italy, Spain and the United Kingdom), who accepted to participate in the study. The data were analyzed using SPSS software version 26.0.ResultsMedian total FATCOD-B scores indicated intermediate levels of students’ attitudes towards care for dying patients, with a statistically significant difference among the three student groups. The median total FATCOD-B scores did not statistically significantly change in students with different age, gender, year of study, religious believes, nursing education on palliative care, previous experiences of dying patient care and personal grieving.ConclusionsIn our study, nursing students feel partially prepared in caring for dying patients and their attitudes do not change as the course of study progresses. No selected variables had an impact on students’ attitudes towards palliative care. Since nurses play a vital role in ensuring the quality of care, education on end-of-life care should be offered as a core part of undergraduate nursing programs.